The Effect of Audio-Lingual Method Toward Teaching Speaking Ability in Private English Course - Relis Aqilatul Ma'rifah (Universitas Negeri Surabaya, 2023)
Abstract: This study aimed to determine the effectiveness of the audio-lingual method on teaching speaking English in the English course Pare. This type of research is quantitative research using the Pretest-Posttest One-Group Design. The results of the analysis of the pretest and posttest learning outcomes data with the t-test were obtained with an average pretest score of 62.2 and an average posttest score of 80.13. With N = 15, obtained tcount = 6.881 with a significant level of 5% of 2.035. Because tcount = 5.676 > ttable = 2.048 then this shows that the t-test has a significant effect. This shows that there is an effect of the audio-lingual method. The suggestion that researchers can convey is that teachers must always be updated, be more creative and innovative in carrying out classroom learning in order to increase the activeness and learning interest of students in participating in learning. Such as the application of methods that are integrated in technology to the audiolingual method, where itself has structural patterns that use repeated exercises such as pattern drills with practical features it is a self-service. Keywords: Audio-lingual, speaking ability, teaching English.